2007
DOI: 10.1177/0149206307302549
|View full text |Cite
|
Sign up to set email alerts
|

Situation Invisibility and Attribution in Distributed Collaborations

Abstract: This article expands theoretical and empirical understanding of interpersonal relationships under distributed conditions by highlighting the importance and consequences of situation invisibility. In a laboratory study, the authors demonstrate that distributed teammates are significantly more likely than collocated teammates to make internal dispositional attributions rather than situational attributions concerning negative partner behavior because of situation invisibility. These dispositional attributions in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
55
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 60 publications
0
55
0
Order By: Relevance
“…As such, construal level theory provides an alternate explanation for why distributed team members are more inclined to make person-based attributions about their fellow team members (Cramton, 2001;Cramton et al 2007). …”
Section: Proposition 2: There Will Be Less Variance In Perceptions Ofmentioning
confidence: 99%
“…As such, construal level theory provides an alternate explanation for why distributed team members are more inclined to make person-based attributions about their fellow team members (Cramton, 2001;Cramton et al 2007). …”
Section: Proposition 2: There Will Be Less Variance In Perceptions Ofmentioning
confidence: 99%
“…Information regarding the work context of team members is not easily available to members of a virtual team (Cramton, 2001;Hinds & Weisband, 2003), and members are often in ignorance of others' actions (Gutwin & Greenberg, 2002), which can lead to attribution errors. Cramton et al (2007), for example, reported that members of virtual teams are more likely to make internal dispositional attributions, opposed to members of collocated teams that tend to make situational attributions, about the negative behavior of team partners. Cramton and colleagues sensemaking, which leads to personal understandings and personal mental models as eloquently described by Weick and his colleagues (Weick, 1979;.…”
Section: Team Mental Models Team Performance and Team Outcomesmentioning
confidence: 99%
“…In virtual teams the interpretation of events was shown by Cramton et al (2007) to create attributions about teammates, which can evoke emotions toward these teammates. Suppose, for example, a teammate is said to not have completed assigned work; attributing this to laziness would likely lead to anger (Smith and Ellsworth, 1985).…”
Section: Team Mental Models Team Performance and Team Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…In so far as research has addressed the effects of reduced working in the same location at set hours, attention typically has gone to issues of communication (Nardi & Whittaker, 2002), attribution (Cramton, 2002;Cramton et al, 2007), self-control (Clegg & Van Iterson, 2013), and conflict (Carmel, 1999;Hinds & Mortensen, 2005;Hinds & Bailey, 2003). In addition, perceptions of proximity in virtual work have been addressed (Wilson et al, 2008) as well as, obviously, individual and group performance of distributed work arrangements (Ahuja et al, 2003;Maznevski & Chudoba, 2000;Shin, 2004).…”
mentioning
confidence: 99%